Resolution Of Labor Legal Problems Between Companies And Employees Through Mediation With Trade Unions Throughhout Indonnesia (Case Study At PT. Sawit Panen Terus) - Ega Dwi Amanda; Siti Nurhayati; Mochammad Erwin Radityo (JURNAL HUKUM SEHASEN, 2026)
Industrial relation between companies and employees are a fundamental factor in the world of employment that must be built on a sense of balance, fairness, and mutual respect. However, in practice, disputes between the two parties are not uncommon. The settlement of industrial relations disputes through mediation is a process in which the parties resolve their issues with the assistance of a neutral mediator. Mediation in the settlement of industrial relations disputes is an effective method because it provides the parties involved with greater access to the outcome compared to arbitration or court proceedings. This study aims to discuss the Procedure for Settling Industrial Relations Disputes and the Effectiveness of Mediation-Based Settlement of Industrial Relations Disputes by the All-Indonesia Workers Union as a mediator, using a case study at PT Sawit Panen Terus. The research method used is empirical juridical, namely a case study approach. The results of this study indicate that mediation is effective, as industrial problems are resolved peacefully. The agreements reached must be carefully implemented by both parties involved.